Black woods, blue sky eaudiobook A novel. - Ivey, Eowyn (Books on Tape, 2025)
NATIONAL BESTSELLER • The author of the Pulitzer Prize finalist The Snow Child returns to the mythical landscapes of Alaska with an unforgettable dark fairy tale that asks the question: Can love save us from ourselves? “No one writes like Eowyn Ivey.”—Geraldine Brooks “You will find yourself in places you have never been.”—Louise Erdrich “Ivey is an enthralling storyteller.”— The New York Times Book Review Birdie’s keeping it together; of course she is. So she’s a little hungover, sometimes, and she has to bring her daughter, Emaleen, to her job waiting tables at an Alaskan roadside lodge, but she’s getting by as a single mother in a tough town. Still, Birdie can remember happier times from her youth, when she was free in the wilds of nature. Arthur Neilsen, a soft-spoken and scarred recluse who appears in town only at the change of seasons, brings Emaleen back to safety when she gets lost in the woods. Most people avoid him, but to Birdie, he represents everything she’s ever longed for. She finds herself falling for Arthur and the land he knows so well. Against the warnings of those who care about them, Birdie and Emaleen move to his isolated cabin in the mountains, on the far side of the Wolverine River. It’s just the three of them in the vast black woods, far from roads, telephones, electricity, and outside contact, but Birdie believes she has come prepared. At first, it’s idyllic and she can picture a happily ever after: Together they catch salmon, pick berries, and climb mountains so tall it’s as if they could touch the bright blue sky. But soon Birdie discovers that Arthur is something much more mysterious and dangerous than she could have ever imagined, and that like the Alaska wilderness, a fairy tale can be as dark as it is beautiful. Black Woods, Blue Sky is a novel with life-and-death stakes, about the love between a mother and daughter, and the allure of a wild life—about what we gain and what it might cost us.